ALIH KODE DAN CAMPUR KODE PADA PENGGUNAAN BAHASA ACEH RAGAM LISAN SISWA KELAS VII SMPN KOTA LHOKSEUMAWE (The Over Code and the Mix Code of the Usage of Acehnese Language Variety Spoken for Students Class VII SMP Lhokseumawe) - Ramli, Ramli (Jurnal Mentari, 2012)
Juni Ahyar Unimal, Lhokseumawe Ramli FKIP Universitas Syiah Kuala, Darussalam, Banda Aceh   ABSTRACT The use of local languages ​​among teenagers, especially for students class VII SMP Negeri 7 Lhokseumawe, the spotlight observer language. Observers attempt to deduce a variety of language problems that occurred in the use of the vernacular. That is what researchers raise an issue in this study. This study aims to (1) describe the over code and mix code on the use of a variety of oral Acehnese language for students class VII SMP Negeri 7 Lhokseumawe and (2) describe social factors determining of the over code and mix code on the use of a variety of oral Aceh language for students class VII SMP Negeri 7 Lhokseumawe. Sources of data/data of this study is the students class VII of SMP Negeri 7 Lhokseumawe. The data was collected using observation techniques and interviews. These results indicate that the use of Acehnese language for students class VII of SMP Negeri 7 Lhokseumawe as seen from the base language obtained the over code and mix code in two variations, namely (1) the over code and mix code with the basic of Aceh language and (2) the over code and mix code with the basic of Indonesian language. Over code in students class VII SMP Negeri 7 Lhokseumawe there are several types of variations in the form of over code are (1) the over code of metaphorical, (2) the over code of situational, (3) the over code of internal, and (4) the over code of temporary. The mix code contained in students class VII SMP Negeri 7 Lhokseumawe only be inner code-mixing. Social factors that affect the over code either (1) speakers, (2) the opponent, (3) the presence of a third speaker, (4) the situation, and (5) the subject, while the social factors that influence the mix code are (1) the attitude of speakers and (2) the limitations of words. Key words: over code, mix code, Acehnese Language  DAFTAR  PUSTAKA Arikunto, Suharsimi. 1998. Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta. Bloomfield, Leonard. 1995. Language ‘Bahasa’. Jakarta: Gramedia Pustaka Utama. Chaer, Abdul dan Leonie Agustina. 2004. Sosiolinguistik Perkenalan Awal.   Jakarta: Rineka Cipta. Finoza, Lamuddin. 2004. Komposisi Bahasa Indonesia. Jakarta: Diksi. Ibrahim, Ridwan dan Wildan (Ed.). 2003. Bahasa Indonesia Perguruan Tinggi.  Banda Aceh: Geuci. Iskandar, Denni. 2010. “Menunda Punahnya Bahasa Aceh”. Dalam Serambi           Indonesia, Edisi 12 Juni 2010. Diakses tanggal 10 Oktober 2011. http://gemasastrin.wordpress.com. Keraf, Gorys. 2004. Diksi dan Gaya Bahasa. Jakarta: Gramedia Pustaka Utama. Kushartanti dkk.. 2005. Pesona          Bahasa Langkah Awal Memahami     Linguistik. Jakarta: Gramedia Pustaka Utama. Mahsun, 2005. Metode Penelitian Bahasa. Jakarta: Raja Grafindo Persada. Nababan, P.W.J. 1993. Sosiolinguistik Suatu Pengantar. Jakarta: Gramedia. Ohoiwutun, Paul. 2002. Sosiolinguistik: Memahami Bahasa dalam Konteks Massyarakat dan Kebudayaan. Jakarta: Visipro. Rahardi,  R.  Kumjana.  2001.  Sosiolinguistik,  Kode  dan  Alih  Kode.      Yogyakarta: Pustaka Pelajar Offset. Rahardi, Kunjana. 2010. Kajian Sosiolinguistik: Ihwal Kode dan Alih Kode.   Bogor: Ghalia Indonesia. Sibarani, Robert. 1992. Hakikat Bahasa. Bandung: Citra Aditya Bakti. Sumarsono dan Paina Partama. 2004. Sosiolinguistik. Yogyakarta: Pustaka Pelajar dan Sabda. Suwito. 1996. Sosiolinguistik Pengantar Awal. Surakarta: Henary Offset.